2020
DOI: 10.3390/pharmaceutics12020166
|View full text |Cite
|
Sign up to set email alerts
|

A 3D Bioprinted Pseudo-Bone Drug Delivery Scaffold for Bone Tissue Engineering

Abstract: A 3D bioprinted pseudo-bone drug delivery scaffold was fabricated to display matrix strength, matrix resilience, as well as porous morphology of healthy human bone. Computer-aided design (CAD) software was employed for developing the 3D bioprinted scaffold. Further optimization of the scaffold was undertaken using MATLAB® software and artificial neural networks (ANN). Polymers employed for formulating the 3D scaffold comprised of polypropylene fumarate (PPF), free radical polymerized polyethylene glycol- polyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…The matrix analysis showed that after the application of the scaffolds, the fractured bone had similar matrix hardness and matrix resilience to healthy human clavicle bones. This highlights the potential for bioprinted pseudo bone scaffolds to fill in fracture sites, resulting in great adhesion of the fractured bone and restoration to intended mechanical strength [11].…”
Section: Three-dimensional Bioprintingmentioning
confidence: 99%
“…The matrix analysis showed that after the application of the scaffolds, the fractured bone had similar matrix hardness and matrix resilience to healthy human clavicle bones. This highlights the potential for bioprinted pseudo bone scaffolds to fill in fracture sites, resulting in great adhesion of the fractured bone and restoration to intended mechanical strength [11].…”
Section: Three-dimensional Bioprintingmentioning
confidence: 99%
“…Recently, a 3D bioprinted pseudo-bone drug delivery scaffold for simvastatin was generated to promote bone healing. This scaffold displayed matrix strength, matrix resilience, and porous morphology of healthy human bone [ 203 ].…”
Section: Bioprinting Processmentioning
confidence: 99%
“… ( i ) Schematic diagram of stereolithography (SLA) printer setup [ 63 ]. ( ii ) ( A ) Proposed 3D model, ( B ) macroscopic view of SLA-printed scaffolds containing PTMC only and PTMC with two varying ratios of HA respectively and ( C ) representative SEM images of the SLA-printed scaffolds [ 64 ]. ( iii ) A rapid prototype generation starting from MR images, the triangulated mesh is generated.…”
Section: Figurementioning
confidence: 99%